2007
DOI: 10.1038/sj.embor.7401031
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of RNA and TAP binding to SF2/ASF

Abstract: The serine/arginine-rich (SR) protein splicing factor 2/alternative splicing factor (SF2/ASF) has a role in splicing, stability, export and translation of messenger RNA. Here, we present the structure of the RNA recognition motif (RRM) 2 from SF2/ASF, which has an RRM fold with a considerably extended loop 5 region, containing a two-stranded b-sheet. The loop 5 extension places the previously identified SR protein kinase 1 docking sequence largely within the RRM fold. We show that RRM2 binds to RNA in a new wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
127
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(144 citation statements)
references
References 23 publications
(41 reference statements)
10
127
0
Order By: Relevance
“…An arginine-rich motif is essential for TAP interaction with 9G8, SRp20, and SF2/ASF (12,13). Therefore, we assessed whether arginines present within REF amino acids 16-36 were required for TAP binding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An arginine-rich motif is essential for TAP interaction with 9G8, SRp20, and SF2/ASF (12,13). Therefore, we assessed whether arginines present within REF amino acids 16-36 were required for TAP binding.…”
Section: Resultsmentioning
confidence: 99%
“…In this assay, the activity of an export factor is monitored by tethering it to an inefficiently exported reporter mRNA via bacteriophage MS2 coat protein (MS2) and RNA operator sequences (13) (Fig. 2E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assays were carried out as described in Hargous et al (2006) and Tintaru et al (2007), with the exception that renilla luciferase rather than ß-galactosidase was used for the normalization of transfection efficiency. For each transfection, 700 ng of each of the plasmids encoding the MS2-protein, 50 ng of luc-RRE firefly construct, and 5 ng of pRL-TK, a thymidine kinase renilla luciferase control vector, were cotransfected in 24-well plates.…”
Section: Tethered Mrna Export Assaymentioning
confidence: 99%
“…This raises the possibility that multiple and partially redundant adaptor proteins may be responsible for the recruitment of NXF1. Indeed, spliceosomal proteins, including U2AF35 (Zolotukhin et al, 2002) and some members of the SR family of splicing factors, were shown to interact with NXF1 and act as adaptors for NXF1-dependent export of poly(A) mRNAs (Huang and Steitz, 2001;Huang et al, 2003;Lai and Tarn, 2004;Hargous et al, 2006;Tintaru et al, 2007).…”
Section: Introductionmentioning
confidence: 99%